Limits and Barriers of Neodevelopmentalism: Lessons from the Argentinean Experience, 2003-2011 - Féliz, Mariano (2015)
Neodevelopmentalism has become Argentina’s hegemonic development project after neoliberalism. While it has been able to bring back economic growth, the development of its inner contradictions is creating growing barriers to the possibility of further expansion within the same project of development, particularly as the world economy enters into crisis. I analyze the constitution of the hegemonic project and the main barriers it faces.